Study on the weighting of building acoustics descriptors and their influence on the quality of acoustic comfort for the occupants - Silva, R. (2014)
It was recently created in Portugal a methodology for residential building acoustics classification. This methodology takes into account three levels of evaluation, being one of them, the dwelling. To evaluate the dwelling are considered eight descriptors which are weighted by specific coefficients in order to establish a differential influence of each descriptor in the dwelling’s final evaluation score. This paper focus on a detailed analysis on the reliability of these weighting coefficients as values that are supposed to reflect the population complains related to the various types of sounds (neighboring; external; equipment) they are exposed to, and so that on which descriptors have more or less influence in the acoustic comfort provided by the dwelling. The magnitude of these coefficients was studied and obtained through a social survey, conducted using a fill tool on-line. Based on the obtained results, it was possible to define a set of adequate values for these coefficients, and thus compare them with the ones established on the acoustic evaluation scheme for residential buildings existing in Portugal.